Clinical Outcomes Are Similar Following Anterior Cervical Discectomy and Fusion Versus Cervical Disc Arthroplasty - Tariq Z. Issa; Junho Song; Omri Maayan; Brian Cho; Yunsoo Lee; Saad B. Chaudhary; Andrew C. Hecht (Clinical Spine Surgery, 2026)
Study Design: Systematic review. Objective: To compare clinical outcomes of anterior cervical discectomy and fusion (ACDF) and cervical disc arthroplasty (CDA) in studies without industry influence. Summary of Background Data: Both CDA and ACDF are appropriate options for cervical degenerative disc disease. However, most studies investigating this have significant industry influence due to either industry sponsorship or conflicts of interest among authors. Methods: A systematic review of all studies investigating CDA versus ACDF in the Cochrane and PubMed/EMBASE databases was performed. Studies were excluded if they were supported by industry without investigator independence, had a minimum follow-up